PENGARUH ERM IMPLEMENTATION, INVENTORY INTENSITY, DAN CORPORATE IMAGE TERHADAP ECONOMIC PERFORMANCE - Eksandy, Arry; Sari, Riski Ulan; Dewanti, Pratiwi (COMPETITIVE, 2021)
This study aims to examine the effect of ERM Implementation, Inventory Intensity and Corporate Image on the Economic Performance of Manufacturing Companies listed on the Indonesia Stock Exchange. This study uses a sample of Manufacturing Companies listed on the Indonesia Stock Exchange during the period 2015 – 2018. Based on the purposive sampling method, the number of Manufacturing Companies sampled in this study were 12 banks. Hypothesis testing using panel data regression analysis using the Eviews 9.0 program. The results of this study indicate that the coefficient of determination (Adjusted R-squared) has a value of 13.9% while the remaining 86.1% is influenced by other factors. The t-test shows that ERM Implementation has no effect on Economic Performance, Inventory Intensity has no effect on Economic Performance, and Corporate Image has no effect on Economic Performance. While the F test shows that together ERM Implementation, Inventory Intensity and Corporate Image have an effect on Economic Performance.